الاستعارة في ضوء البلاغة الجديدة موقع الاستعارة بين النّسق الحجاجيّ والتّجلّي الإعلاميّ (Journal of Humanitarian and Applied Sciences, 2020)
In short, we will try to present an approach between the pilgrims and the pattern. The metaphor, let's then go to the metaphor and the media. What defines metaphor and its importance is the role it plays in the discourse to which they are left.As the metaphor constitutes the purposes and form of the pilgrims of the speech, it has been a means of persuasion since the inception of rhetoric as a means of influencing the audience by using a rhetorical fluid through proof means to make the potential more attractive, and borrowing is one of these rhetorical images as the speaker seeks to convince the recipient and seek to change His intellectual and emotional attitude through the use of different graphic images, as he may resort to employing the creativity and uniqueness of the listener and get him to respond and achieveThat's the communication purpose between them. Not only did the new rhetoric be a linguistic persuasion, but it went beyond it to the linguistic production, from posters and documentaries, or pictures on the pages of newspapers, websites or even music. The communicative performance in the media depends on the success of the media discourse and its ability to influence its audience, as the promoter in the success of his famous speech such as promoting a particular commodity or service to a language commensurate with the souls of the recipients in order to influence them and their appeal towards this propaganda, as it makes it suggestive of a character Thumb to draw more attention such as reading a newspaper or watching cinema, the audio and visual media benefited from the various rhetorical formulas to attract the thought and passion of the recipient and thus formed a coordinated format with all segments of society. Wherever there is a commercial image or poster, the rhetoric is present and effective, and in order to resonate with the public, it has to wear its fancy metaphorical dress to achieve effectiveness.